2016
DOI: 10.4490/algae.2016.31.9.3
|View full text |Cite
|
Sign up to set email alerts
|

The phytohormone abscisic acid increases triacylglycerol content in the green microalga Chlorella saccharophila (Chlorophyta)

Abstract: Microalgae are currently a very promising source of biomass and triacylglycerol (TAG) for biofuels. In a previous study, we identified Chlorella saccharophila as a suitable source of oil for biodiesel production because it showed high biomass and lipid content with an appropriate fatty acid methyl esters profile. To improve the TAG accumulation in C. saccharophila, in this study we evaluated the effect of abscisic acid (ABA) addition on cell concentration, lipid content and TAG production in this microalga. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…In Scenedesmus quadricauda , ABA improved cell growth by 2.1-fold, and induced the accumulation of saturated fatty acids by 12% under nitrogen starvation [ 254 ]. Similar results were reported for Chlorella saccharophila , E. gracilis , and C. saccharophila , following ABA treatment under HM stress [ 255 , 256 ].…”
Section: Genetic Engineering Targets To Improve Microalgal Hm Bioreme...supporting
confidence: 86%
“…In Scenedesmus quadricauda , ABA improved cell growth by 2.1-fold, and induced the accumulation of saturated fatty acids by 12% under nitrogen starvation [ 254 ]. Similar results were reported for Chlorella saccharophila , E. gracilis , and C. saccharophila , following ABA treatment under HM stress [ 255 , 256 ].…”
Section: Genetic Engineering Targets To Improve Microalgal Hm Bioreme...supporting
confidence: 86%
“…In a microalgae S. quadricauda, culture supplemented with 2 µM, ABA increased biomass production 2.1-fold in nitrogen-limited conditions after 48 h of cultivation, so this may be a potential strategy for efficient microalgal cultivation for biofuel production [67]. Meanwhile, lipid accumulation of microalgae with only ABA supplemented has also been revealed [32,33]. It was shown that 1.0 mg/L ABA imposed an augmentation of lipid productivity of C. vulgaris ZF strain and FACHB-31 by 123% and 44%, respectively [32].…”
Section: Abscisic Acidmentioning
confidence: 90%
“…As demonstrated in this research paper, where the best photoperiod for obtaining lipids was 12:12 (Table 1), these results are similar to those obtained in other research papers where they evaluated Chlorella vulgaris, and higher biomass production and lipid content were achieved under 12 h: 12 h light:dark cycles relative to a 24 h: 0 h continuous illumination condition [28]. In Nannochloropsis sp., lipid content and growth rate were highest under an 18 h:6 h light/dark cycle compared with 24 h:0 h and 12 h:12 h cycles [12,22]. In Nannochloropsis gaditana, biomass concentration was highest under a 12 h:12 h light/dark cycle, while lipid content was highest under a 16 h:8 h cycle, relative to 24 h:0 h and 8 h:16 h cycles [9].…”
Section: Discussionmentioning
confidence: 89%
“…Cellular concentration was determined using a Neubauer hemacytometer (Hausser Scientific, Horsham, PA, USA) and a Primo Star microscope (Carl Zeiss, Oberkochen, Germany). The cells were harvested by centrifugation and dried at 70 • C. Growth rate parameters of each treatment were calculated on the basis of cell count during exponential phase of growth [22]. Following growth parameters were calculated from the observed data [23].…”
Section: Growth Kinetics and Biomass Estimationmentioning
confidence: 99%